Analisis Efektifitas Groin terhadap Abrasi Pantai Kampung Tua Nongsa - Suwarlan, Stivani Ayuning; Fernando, Delvin; Oktavino, Farel Cassaro; Tan, Rosalinda; Hura, Wester Maesi; Rangkuty, Gladies Imanda Utami (Arsir, 2023)
The groin is a building construction located on the shore with an orientation that points perpendicularly to the sea. The function of the groin is as a barrier from sediments that move along the coastline and a medium for wave dampening. Changes in coastal areas caused by nature or normal marine activities make coastal areas need to be considered more deeply. The groin construction process that does not apply structural and architectural science or analysis causes the building to be unstable and easily destroyed by large waves. The decline of the coastline in Kampung Tua Nongsa from 1995 to 2022 as far as 30 meters resulted in residential settlements experiencing continuous land shifts. The research method uses descriptive qualitative through interview, observation, and documentation approaches. This research aims to obtain the results of the effectiveness of groins on the coast of Kampung Tua Nongsa by looking at the distribution pattern, structure, material, and architecture. The research results show that groins that are effective for the beach conditions of Kampung Tua Nongsa should be natural stone material with groin lengths of 50 cm - 60 cm and groin heights between 0.5 - 1.0 m.